A new symmetrical Z-shaped compliant linear actuator based on parasitic motion principle. (1st December 2022) - Xie, Yanlin; Li, Yangmin; Cheung, Benny Chifai
Abstract: To meet the demand of designing piezoelectric actuators with long working stroke and high resolution, a new parasitic motion principle (PMP) linear actuator based on the symmetrical Z-shaped compliant mechanism was proposed in this paper. The mechanism design and the operation principle of the proposed linear actuator were elaborated. The theoretical model of the symmetrical Z shaped compliant mechanism deformation was established, and was verified by the simulation analysis. Experimental studies were conducted on a manufactured prototype to investigate the performances of the proposed linear actuator. The results indicate that a linear actuator with bi-directional motion can be achieved, which has a resolution of 106 nm in the forward direction and 84 nm in the reverse direction. Under the locking force of 0.8 N, the maximum speed of 270 µ m s −1 was reached, when the amplitude and the frequency of the driving voltage were set to 60 V and 650 Hz. It is also noted that the proposed linear actuator can work with a loading capacity of 25 g. This study has provided an alternative way for the development of a PMP linear actuator with bi-directional motion.